2010
DOI: 10.1111/j.1742-481x.2010.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

A simple and effective approach for the treatment of diabetic foot ulcers with different Wagner grades

Abstract: Diabetic foot infections are the major cause of morbidity. Infection is the common sequel of diabetic foot ulceration that leads to delayed wound healing. These infections are difficult to control. If not addressed well in time, they may lead to amputation of foot. An attempt has been made to develop simple and effective treatment modality by using citric acid as a sole antimicrobial agent to control diabetic foot infections not responding to conventional treatment. Hundred and fifteen cases of diabetic foot u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…Nagoba et al 13 observed that citric acid treatment promoted healing after 16-34 applications, and that this was highly effective for controlling infections and for successfully managing diabetic foot ulcers without deep osteomyelitis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nagoba et al 13 observed that citric acid treatment promoted healing after 16-34 applications, and that this was highly effective for controlling infections and for successfully managing diabetic foot ulcers without deep osteomyelitis.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 This small number of studies may be due to difficulty in monitoring diabetic patients from the onset of the infection until wound healing, thus making it complex to obtain a homogeneous sample. It is also due to difficulties in obtaining a diagnosis of infection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations